Guinness World Records, 2003 - Folkard, Claire (New York : Bantam Books, 2003)
Presents the biggests, smallests, fastests, longests, and other record setters for 2003 in such categories as the human body, human achievement, amazing feats, entertainment, technology, and sports.
Includes index.
Young Adult
Keywords: Curiosities and wonders; World records; Curiosities and wonders; World records